DETERMINATION OF THE STABILITY CONSTANT OF COMPLEX BIS(1, 1-DIETHYL-3-BENZOILTIOUREATO)LEAD(ll) - Angulo-Cornejo, J. (2000)
The synthesis of Bis[1,1-diethyl-benzoylthioureathe]lead(II)complex, Pb[PhCONCSNEt2]2 and has been characterized by elementary analysis and IR spectra; the complex has a global formula C24H30ON2S2Pb with number of coordination 4; as well as, binding is double-toothed, coordinating by oxygen and sulphur. In the aquo-dioxane system, has been determined the acid constan! of 1, 1-diethyl-3-benzoylthioureathe ligand, Ka=9,31*1O^(-10), pKa=9,03 with ionic force of the dissolution μ=0.2, contributed by the ionic salt of KHN03 . The constan! of stability of the Bis[1, 1-diethylbenzoilthioureathe]lead(II), Pb[PhCONCSN(Et)2]2, K1= 2,35x10^(-6) ; K2=1,17x10^(6), logB1=6,37; logB2=12,44 through the semi-ñ method.